Efektivitas Penekanan Titik Akupresur Terhadap Pengurangan Nyeri Persalinan - Fadila Septi Hasanah; Nova Yulita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Labor pain occurs due to the contraction of uterine muscles, which can cause discomfort and pain for the mother, potentially affecting the labor process. Acupressure is a complementary therapy that involves applying pressure or massage and stimulation at specific points on the body. The purpose of this study is to determine the effectiveness of acupressure point pressure in reducing labor pain for Mrs. N at PMB Silvi Ayu, S.Keb in Pekanbaru. This research used a descriptive method with a case study design. The results of this study indicate that acupressure point pressure is proven to be effective in reducing pain during labor, especially in the active phase. This method is safe and can be used as an alternative or complementary approach to other pain management methods.